An ultrastructural study of the urinary bladder in children correlated with histological, bacteriological, and clinical findings. Issue 3 (March 1975) - Haynes, M; Trott, P A; Islam, A K; Hirst, G
Abstract : Bladder biopsies from six boys without a history of urinary tract infection were taken during hypospadias repair operations and examined by electron microscopy. The ultrastructure of the epithelium, which was presumed to represent the normal, is described in detail and compared with the reported findings in other mammalian species. The appearances are generally similar although in our material the luminal membrane of the superficial cells was thicker than that surrounding the other epithelial cells but not asymmetrical. We observed membrane-coating granules which have not been reported before in bladder epithelium. The appearances of the normal bladder are compared to those seen in 24 children with urinary infection. In the presence of acute infection in large heterogeneous secondary lysosomes which are present in the intermediate and superficial cells of the normal bladder are reduced in number and the amount of rough endoplasmic reticulum is increased.